(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Diabetes mellitus is a diseases of worldwide importance, the incidence and complications of this disease became an increasing problem. In Basrah,southern Iraq, the prevalence of DM is very high . Diabetic foot is a source of significant morbidity and change in quality of life for diabetic patients. Objectives: To describe the characteristics of sample of patients with diabetic foot ulcer who attended Al Fayha Diabetic Foot Clinic and to evaluate the predictors of surgical intervention needed for treatment of these patients especially for those who are in need for amputation. Method: A cross sectional descriptive study conducted in Al Fayha Diabetic Foot Clinic, Basrah, Iraq. From January 2018 until July 2019. It included 73 adult patients suffering from diabetic foot ulceration : 29 (39.7%) male patients and 44 (60.3%) female patients. Results: The mean age was 52.86 years. The study included 71 patients with type 2 diabetes (97.3%) and 2 patients with type 1 diabetes (2.7%).The mean duration of symptoms was approximately one month. More than half of the cases who underwent debridement had wounds of grade 2 (University of Texas Classification) while 88% of cases who underwent amputation had wounds of grade 3. In the group of patients who underwent debridement, 41 cases (85.4%) had moderate infection (IDSA), while for those who underwent amputation, 16 cases (64%) had severe infection and this difference was statistically significant (p value ?0.001). Conclusions: The majority of patients were females (60%),the age group of 50 years and above constitutes more than half of the cases,almost 80% have the disease for more than 10 years,all cases showed evidence of uncontrolled disease. Wound stage (UT Classification) and IDSA severity of wound infection were the predictors for surgical intervention in patients suffering from diabetic foot ulcers in Basrah.